Preimplantation Genetic Diagnosis in Marfan Syndrome. (27th May 2013) - Vlahos, N. F.; Triantafyllidou, O.; Vitoratos, N.; Grigoriadis, C.; Creatsas, G.
Abstract : Marfan syndrome (MFS) is a systemic hereditable disorder of the connective tissue with mainly cardiovascular manifestations, such as aortic dilatation and dissection. We describe a case of a 32-year-old Caucasian woman, clinically asymptomatic with MFS who presented for genetic consultation to prevent the transmission of disease to her offspring. She underwent controlled ovarian stimulation (COH), in vitro fertilization (IVF) combined with preimplantation genetic diagnosis (PGD), and a singleton pregnancy with positive fetal heart rate was revealed. At 34 weeks' gestation she delivered vaginally a healthy premature male infant weighting 2440 gr. The patient remained asymptomatic during pregnancy, delivery, and 3 months postpartum. It is has to be mentioned that the availability of PGD is essential to prevent the transmission of disease to the next generation.